Questioning the Extreme Neurovirulence of Monkey B Virus (Macacine alphaherpesvirus 1) - R. Eberle; L. Jones-Engel (Advances in Virology)
Monkey B virus (Macacine alphaherpesvirus 1; BV) occurs naturally in macaques of the genus Macaca, which includes rhesus and long-tailed (cynomolgus) monkeys that are widely used in biomedical research. BV is closely related to the human herpes simplex viruses (HSV), and BV infections in its natural macaque host are quite similar to HSV infections in humans. Zoonotic BV is extremely rare, having been diagnosed in only a handful of North American facilities with the last documented case occurring in 1998. However, BV is notorious for its neurovirulence since zoonotic infections are serious, usually involving the central nervous system, and are frequently fatal. Little is known about factors underlying the extreme neurovirulence of BV in humans. Here we review what is actually known about the molecular biology of BV and viral factors affecting its neurovirulence. Based on what is known about related herpesviruses, areas for future research that may elucidate mechanisms underlying the neurovirulence of this intriguing virus are also reviewed.